Analisis Kelayakan Usaha Budidaya Udang Vaname (Litopenaeus Vannamei) pada Tambak Tradisional di Kecamatan Sibulue Kabupaten Bone - Zailan, Ahmad; Halim, Hasriliandi; Riskiyani, Riskiyani; Astaman, Putra (Agriculture and Socio-Economic Journal, 2025)
This study aims to determine the feasibility analysis of vaname shrimp farming (Litopenaeus Vannamei) in traditional ponds in Sibulue District, Bone Regency. The population in this study is the community of vaname shrimp farming in Sibulue District. Determination of the sample in this study using purposive sampling technique by selecting vaname shrimp farmers who still use traditional methods in the process of cultivation with the characteristics of the area (1) the average land between 0.5 - 5 hectares, (2) the depth of the pond between 50 - 100 meters, (3) the number of stocking between 1-5 heads / m², and (4) feeding techniques using natural feed (without manufactured feed). The number of samples in this study was 67 people. The data analysis used is using the R/C Ratio analysis method, Net Present Value (NPV), Payback Period (PP), Internal Rate Ratio (IRR), Break Even Point (BEP). Based on the results of the analysis, the total cost value was obtained as much as Rp. 30,212,162, and the income value was Rp. 3,287,838. The results of the R / C Ratio analysis with a value of 1.11., Net Present Value (NPV) with a value of 38,524,948, Payback Period (PP) with a value of 1.8., Intern Rate Ratio (IRR) with a value of 49%, and Break Even Point (BEP) with a value of 3.5. From the results of the analysis, it can be concluded that the vaname shrimp farming business on traditional ponds in Sibulue District is feasible to implement.